Thyrotropin receptor, still much to be learned from the patients. Issue 2 (April 2018) - Briet, Dr. Claire; Suteau-Courant, Valentine; Munier, Mathilde; Rodien, Prof. Patrice
Abstract : In the absence of crystal available for the full-length thyrotropin receptor, knowledge of its structure and functioning has benefitted from the identification and characterization of mutations in patients with various thyroid dysfunctions. The characterization of activating mutations has contributed to the elaboration of a model involving the extracellular domain of the receptor as an inverse tethered agonist which, upon binding of the ligand, relieves the transmembrane domain from an inhibiting interaction and activates it. The models derived from comparisons with other receptors, enriched with the information provided by the study of mutations, have proven useful for the design of small-molecule agonists and antagonists that may be used in the future to treat thyroid dysfunctions. In this review, extrathyroidal expression of the thyrotropin receptor is described, the role of which is still poorly defined.